Type II Natural Killer T Cells Contribute to Protection Against Systemic Methicillin-Resistant Staphylococcus aureus Infection - Genardi, Samantha; Visvabharathy, Lavanya; Cao, Liang; Morgun, Eva; Cui, Yongyong; Qi, Chao; Chen, Yi-Hua; Gapin, Laurent; Berdyshev, Evgeny; Wang, Chyung-Ru (Frontiers in Immunology, 2020)
Methicillin-resistant Staphylococcus aureus (SA) bacteremia is responsible for over ten thousand deaths in the hospital setting each year. Both conventional CD4+ T cells and  T cells play protective roles in SA infection through secretion of IFN- and IL-17. However, the role of other unconventional T cells in SA infection is largely unknown. Natural killer T (NKT) cells, a subset of innate-like T cells, are activated rapidly in response to a wide range of self and microbial lipid antigens presented by MHC I-like molecule CD1d. NKT cells are divided into two groups, invariant NKT (iNKT) and type II NKT cells, based on TCR usage. Using mice lacking either iNKT cells or both types of NKT cells, we show that both NKT cell subsets are activated after systemic SA infection and produce IFN- in response to SA antigen, however type II NKT cells are sufficient to control bacterial burden and inflammatory infiltrate in infected organs. This protective capacity was specific for NKT cells, as mice lacking mucosal associated invariant T (MAIT) cells, another innate-like T cell subset, had no increased susceptibility to SA systemic infection. We identify polar lipid species from SA that induce IFN- production from type II NKT cells, which requires both CD1d-TCR engagement and IL-12 production by antigen presenting cells. We also demonstrate that a population of T cells enriched for type II NKT cells are increased in PBMC of SA bacteremic patients compared to healthy controls. Therefore, type II NKT cells perform effector functions that enhance control of SA infection prior to conventional T cell activation and recognize SA-derived lipid antigens. As CD1d is highly conserved in humans, these CD1d-restricted SA lipid antigens could be used in the design of next generation SA vaccines targeting cell-mediated immunity.